Globalization and the urban poor - Janice E. Perlman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The focus of this paper is the effect of contemporary globalization on poverty and inequality in cities of the `global south'. Specifically it addresses the impact of globalization on marginalized communities—slums, squatter settlements and shantytowns—collectively called `informal settlements'. This is a timely issue given that over the next 25 years virtually all of the population growth worldwide will be in the cities of developing countries largely concentrated in such settlements. The paper takes a critical look at current assumptions about globalization, urban poverty, and inequality, distinguishing between different constructs and aspects of globalization and separating causality from co-terminality. It questions how the informal sector would fare in the face of advanced capitalism and technological transformations, absent the global component. Using Brazil as an example the paper draws comparisons between the lives of the poor during the isolationist period of `import substitution' and the military dictatorship and their current lives in the context of pervasive globalization of ideas, icons, and identities. The findings are based on a longitudinal panel study conducted in the favelas of Rio de Janeiro between 1968 and 2005, examining the changes over time, space and generations. The presumed effects of globalization on the lives of the urban poor, on the levels of inequality between them and the rest of the city and on public policy are thrown into question. The answers are sought in the people's perceptions of the impact of globalization on their lives, in the historic transformations of the country and city, and in the life history, survey data and open-ended interviews collected over this 35- year period.
Keywords: R11; I32; 330; urban poverty; globalization; favelas; inequality; exclusion; violence; public policy; longitude research; Brazil; Rio de Janeiro; Städtische Armut; Stadtentwicklung; Globalisierung; Brasilien; Rio de Janeiro